(untitled) (Progress Annals: Journal of Progressive Research, 2024)
The article is about the influence of fine art in color studies and painting classes, the influence of students on the human psyche, helping people to heal people symbolically through color, finding education, giving philosophical thoughts through color circles, knowing and enriching the inner world of a person through color, achromatic and methodical recommendations are given on the issues of extensive study of chromatic colors, helping to form the spirituality of people.